Mystagogical Philosophy as Itinerary: Christian Wisdom in the Slavic Primary Chronicle - Semenikhin, Nikita (Diakrisis, 2025)
This article rereads Prince Vladimir's conversion narrative (years 986-988, Kievan Rus') in the Primary Chronicle as a patristic mystagogy (a deliberately staged itinerary of purification, illumination and union). Using a participatory-symbolic hermeneutic grounded in Gregory of Nyssa, Dionysius the Areopagite and Maximus the Confessor, it argues that Kievan Rus' first encountered Christianity as a philosophical way of life that unites reason and revelation and culminates in theosis. In this study, "philosopher" is defined as the one who mediates between human inquiry and divine wisdom through a life aimed at likeness to God. St. Maximus the Confessor and St. Cyril-Constantine frame it as knowing "divine and human things" in an eros-driven ascent that is verified in deeds. In the Chronicle, the unnamed "Greek Philosopher" functions precisely so. Moreover, the article shows how dialogue functions as a performative engine transforming persons and positions the Chronicle within the canon of Christian philosophy in Rus'.